Edinburgh companion to Hugh MacDiarmid - Lyall, Scott; McCulloch, Margery Palmer (Edinburgh companions to Scottish literature., 2011)
The only full-length companion available to this distinctive and challenging Scottish poet. By using previously uncollected creative and discursive writings, this international group of contributors presents a vital updating of MacDiarmid scholarship. They bring fresh insights to major poems such as A Drunk Man Looks at the Thistle, To Circumjack Cencrastus and In Memoriam James Joyce, and offer new political, ecological and science-based readings in relation to MacDiarmid's work from the 1930s. They also discuss his experimental short fiction in Annals of the Five Senses, the autobiographical Lucky Poet, and a representative selection of his essays and journalism. They assess MacDiarmid's legacy and reputation in Scotland and beyond, placing his poetry within the context of international modernism. Key Features. Links MacDiarmid's work and influence to recent writings on national identity, transnationalism, postcolonialism and modernity versus tradition Provides close readings of the formal detail of texts and new readings in ecological and science-based contexts Contributes to a re-drawing of the map of literary modernism Contributors include Louisa Gairn (Helsinki), Alan Riach (Glasgow University), Carla Sassi (Verona University), Jeffrey Skoblow (Southern Illinois University), and Michael H. Whitworth (Oxford University).